Pengaruh Frekuensi Dan Durasi Bermain Game Online Terhadap Tingkat Stress Dan Kesejahteraan Psikologis Mahasiswa - Mufid Gilang Al Rifqi; Muhammad Rizky Fernanda (PT. Saha Kreasi Indonesia, 2026)
This study aims to analyze the effect of online game playing frequency and duration on stress levels and psychological well-being in college students. The development of digital technology has increased the popularity of online games among college students, potentially having both positive and negative impacts on their mental health. Using a quantitative approach using a survey method, data was collected from a number of college students who actively play online games. Statistical analysis will be used to test hypotheses regarding the relationship between online game playing patterns (frequency and duration) and indicators of stress (e.g., perceived stress scales) and psychological well-being (e.g., subjective well-being scales). The results of this study are expected to provide a deeper understanding of the impact of online game playing on college students and provide a basis for developing appropriate interventions to promote a balance between gaming activity and optimal mental health.